ABOUT THE CAUSES OF AGRICULTURE CRISIS IN THE REPUBLIC OF SERBIA - Pejanović, Radovan; Glavaš-Trbić, Danica; Tomaš-Simin, Mirela (Economics of Agriculture, 2013)
Agriculture of the Republic of Serbia is in the long-term and the multiple crisis: crisis of management, organization crisis, financial crisis, crisis of competitiveness, investment crisis, market crisis, crisis of agricultural policy, crisis of confidence and other forms of crisis. The aim of this paper is to investigate many causes of the limitations of agricultural development of the Republic of Serbia, where the authors specifically point out the following: unfavorable agrarian structure and the lack of organization of farmers; unregulated market of agricultural products; lack of competitiveness; inadequate role of the state; deagrarisation and depopulation of villages. A qualitative method of analysis, synthesis and comparison, as well as supporting quantitative statistical methods were used. Authors concluded that systematic and radical measures and actions are needed at the macro and micro level, in order to overcome a difficult situation in which our agriculture is, as a strategic activity of the Republic of Serbia.